Anti-inflammatory chromone alkaloids and glycoside from Dysoxylum binectariferum. Issue 42 (18th October 2017) - Kumar, Vikas; Gupta, Mehak; Gandhi, Sumit G.; Bharate, Sonali S.; Kumar, Ajay; Vishwakarma, Ram A.; Bharate, Sandip B.
Graphical abstract: Highlights: A new chromone alkaloid chrotacumine K isolated. Schumaniofioside A reported for the first time from Meliaceae family. Biological evaluation of isolated compounds performed. Chrotacumine K showed potent inhibition of TNF-alpha and IL-6. Physicochemical properties were determined for bioactive compounds. Abstract: Herein we report isolation of a new chromone alkaloid chrotacumine K (12 ) from fruits and a chromone glycoside schumaniofioside A (13 ) from leaves of Dysoxylum binectariferum Hook f. Schumaniofioside A is reported for the first time from Meliaceae family. Other known alkaloids isolated include rohitukine (1 ) and chrotacumine E (6 ). The structure of new alkaloid12 was elucidated on the basis of extensive 1D and 2D NMR analysis, synthesis and chemical hydrolysis. Chemically, chrotacumine K (12 ) is a 3′- O -acetyl rohitukine which on chemical or enzymatic hydrolysis produces rohitukine. The new alkaloid12 is also present in seeds and stem-barks of this plant. The glycoside schumaniofioside A (13 ) is present only in leaves, and in abundance (∼1% w/w of dried leaves). The isolated compounds and extracts were evaluated for in vitro effect on the proinflammatory cytokines (TNF-α and IL-6) in human monocytic THP-1 cells. The alkaloid12 displayed potent inhibition (57%) of TNF-α at 0.3 µM, and was non-toxic to THP-1 cells up to 40 µM, indicating its excellent therapeutic window. Furthermore, a nitrobenzoyl ester analog15e showed better inhibition of IL-6 than parent natural product chrotacumine K.